EFFECTIVENESS OF LEARNING WITH GUIDED DISCOVERY METHOD ON MATHEMATICAL LEARNING OUTCOMES OF CLASS VII SMP - Yoga Dwi Kurniawan; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
This study aims to determine whether there are differences in students' mathematics learning outcomes using guided discovery methods and the expository method. These populations in the study were the students of two classes. The design of this study uses Randomized Pretest-Postest Comparison Group Design. The technique of collecting data uses a test in the form of an essay. The test instrument used is a validity test. The data analysis technique used is the analysis prerequisite test, including the normality test and homogeneity test followed by hypothesis testing. The results of the experimental and control class hypothesis tests with a significant level of 5% and dk = 62 indicate that for students' mathematics learning outcomes (posttest) 1) there are differences in students' mathematics learning outcomes by using the guided discovery method and the expository method in class VII students. of State Junior High School (SMP Negeri) 2 Kalasan, 2) Guided Discovery method is more effective than the expository method on students' mathematics learning outcomes of class VII of SMP Negeri 2 kalasan